SQL bible - Kriegel, Alex (Wiley, 2008)
"Combining theory with everyday practicality, this definitive volume is packed with up-to-date information, new features, and explanations you need to get the very most out of SQL and its latest standard. The book is unique in that every chapter highlights how the new SQL standard applies to the three major databases, Oracle 11g, IBM DB2 9.5, and Microsoft SQL Server 2008. The result is a comprehensive, useful, and real-world reference for all SQL users, from beginners to experienced developers."--Jacket